2015
DOI: 10.15242/ijrcmce.e0915008
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of concentration and stirring time on copper extraction process from pregnant liquid solution (PLS), case study: Sungun copper mine

Abstract: Solvent extraction is regarded as one of the most applicable methods of extracting copper from pregnant liquid solution. The amount and quality of copper extraction are depend on various parameters including: the type of extractant, concentration and the stirring time. The current essay considers the amount of copper extraction from the pregnant liquid solution of Sungun copper mine in an approxiate concentration of 3% by chemorex cp150 as an extractant in 10% and 20% concentrations. In addition, the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The gotten data are organized in table (7). The last mentioned shown that with increasing the contact time from 4 to 12 min., the Y extraction efficiency will increase from 89.19 to 99.47% respectively as a result of the increase in the mass transfer from the aqueous phase to the organic phase, as increases the Y 3+ extracted into the organic phase which will result in an increase in the yttrium extraction efficiency (36) . So, the contact time of 12 min., was hence considered as the optimum value for almost complete extraction of Y from the prepared RECl 3 leach liquor.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…The gotten data are organized in table (7). The last mentioned shown that with increasing the contact time from 4 to 12 min., the Y extraction efficiency will increase from 89.19 to 99.47% respectively as a result of the increase in the mass transfer from the aqueous phase to the organic phase, as increases the Y 3+ extracted into the organic phase which will result in an increase in the yttrium extraction efficiency (36) . So, the contact time of 12 min., was hence considered as the optimum value for almost complete extraction of Y from the prepared RECl 3 leach liquor.…”
Section: Effect Of Contact Timementioning
confidence: 99%